Analisis Pengaruh Jarak Pelat Helical Terhadap Daya Dukung Tekan Helical Pile Pada Tanah Gambut - Ralan Ditra; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Helical piles are a type of foundation that come with helical plate in certain number and space. The research will present the results of loading test using constant rate penetration method conducted on peat soil. Data obtained from the test are load and settlement which then interpreted using both terzaghi and method and tangent intersection method. The result shows no proportional correlation between the load capacity of helical pile withsimilar diameter and the increase of helical plate distance. The bearing capacity of helical pile is influenced by the ratio between the space and the diameter of the plate. The aforementioned load tests are compared with the result of bearing capacity calculationusing individual bearing and cylindrical shear method. It is obtained from the result that the bearing capacity of helical foundation is closer to the behaviour of bearing capacityobtained from cylindrical shear method with 0.633 standard of error while the bearing capacity of individual bearing method is close to the result of standard load test with .637 standard of error.Keyword : helical foundation, peat soil, individual bearing, cylindrical shear.